Cry of the seals : A tale of the frozen sea - Lucas, Jeremy (New York : Macmillan publishimg company, 1984)
A Scottish research team makes a treacherous voyage to Newfoundland where they witness the vicious hunting of the beautiful white harp seals
Keywords: Seafaring life -- Juvenile fiction; Biologists -- Juvenile fiction